Activities of municipal sports schools and olympic reserve schools in large cities of Russia (for 2024) - Fitina, L.N.; Serova, N.B.; Burkova, A.M.; Tropina, L.K. (Theory and Practice of Physical Culture, 2026)
Objective of the study is a comprehensive assessment and comparison of the development indicators of basic Olympic sports of sports schools and sports schools of the Olympic Reserve of the city of Ekaterinburg in comparison with cities with a population of one million in 2024 to identify best practices and problem areas. Methods and structure of the study. The study was based on data from the official statistical reporting on the 5-FC form for 2024, provided by sports schools in nine million-plus cities. Methods of comparative, structural and statistical analysis were used. Quantitative and qualitative indicators are analyzed, including the network of institutions, the number of students, financial support and results of sports training. The leading cities in each of the areas have been identified, as well as key factors affecting the effectiveness of sports reserve training. Results and conclusions. A comparative analysis of the development of basic Olympic sports in Ekaterinburg and cities with millions of residents revealed a significant differentiation in the development of the sports training system in the largest cities of Russia. The findings suggest that there is no universal model of success. The effectiveness of training a sports reserve depends on a number of factors: financial security, historically established sports specializations in the region, and management effectiveness. To even out the situation and increase the overall competitiveness of Russian sports, it is advisable to exchange best practices between regions and develop targeted measures to support lagging areas.